Missed Opportunities to Initiate Endoscopic Evaluation for Colorectal Cancer Diagnosis - Singh, Hardeep (2009)
OBJECTIVES: Delayed diagnosis of colorectal cancer (CRC) is among the most common reasons for ambulatory diagnostic malpractice claims in the United States. Our objective was to describe missed opportunities to diagnose CRC before endoscopic referral, in terms of patient characteristics, nature of clinical clues, and types of diagnostic-process breakdowns involved. METHODS: We conducted a retrospective cohort study of consecutive, newly diagnosed cases of CRC between February 1999 and June 2007 at a tertiary health-care system in Texas. Two reviewers independently evaluated the electronic record of each patient using a standardized pretested data collection instrument. Missed opportunities were defined as care episodes in which endoscopic evaluation was not initiated despite the presence of one or more clues that warrant a diagnostic workup for CRC. Predictors of missed opportunities were evaluated in logistic regression. The types of breakdowns involved in the diagnostic process were also determined and described. RESULTS: Of the 513 patients with CRC who met the inclusion criteria, both reviewers agreed on the presence of at least one missed opportunity in 161 patients. Among these patients there was a mean of 4.2 missed opportunities and 5.3 clues. The most common clues were suspected or confirmed iron deficiency anemia, positive fecal occult blood test, and hematochezia. The odds of a missed opportunity were increased in patients older than 75 years (odds ratio (OR) = 2.3; 95% confidence interval (CI) 1.3–4.1) or with iron deficiency anemia (OR = 2.2; 95% CI 1.3–3.6), whereas the odds of a missed opportunity were lower in patients with abnormal flexible sigmoidoscopy (OR = 0.06; 95% CI 0.01–0.51), or imaging suspicious for CRC (OR = 0.3; 95% CI 0.1–0.9). Anemia was the clue associated with the longest time to endoscopic referral (median = 393 days). Most process breakdowns occurred in the provider–patient clinical encounter and in the follow-up of patients or abnormal diagnostic test results. CONCLUSIONS: Missed opportunities to initiate workup for CRC are common despite the presence of many clues suggestive of CRC diagnosis. Future interventions are needed to reduce the process breakdowns identified.